2009
DOI: 10.1186/1472-6823-9-16
|View full text |Cite
|
Sign up to set email alerts
|

Salivary cortisol differs with age and sex and shows inverse associations with WHR in Swedish women: a cross-sectional study

Abstract: Background: Most studies on cortisol have focused on smaller, selected samples. We therefore aimed to sex-specifically study the diurnal cortisol pattern and explore its association with abdominal obesity in a large unselected population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
97
5
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(120 citation statements)
references
References 39 publications
14
97
5
4
Order By: Relevance
“…Previous studies have also indicated that cortisol levels differ between men and women [8]- [11], [12]- [14]. In our study, there were noticed higher levels of salivary and serum cortisol values in the nurses working in the emergency department, compared to the nurses working in the pathology department.…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies have also indicated that cortisol levels differ between men and women [8]- [11], [12]- [14]. In our study, there were noticed higher levels of salivary and serum cortisol values in the nurses working in the emergency department, compared to the nurses working in the pathology department.…”
Section: Discussionsupporting
confidence: 55%
“…Also, in other studies (46,47), no correlation was found between human tissue HSD11B1 expression and age. Moreover, it is known that the hyperactivity of the HPA axis is reported mainly in the elderly people and there are no significant differences during adulthood (48,49). According to our findings, it seems that in severely obese patients without MetS, the downregulation of NR3C1a in the liver as well as the lower expression of HSD11B1 in the VAT might protect them from the development of metabolic consequences of their obesity.…”
Section: European Journal Of Endocrinologymentioning
confidence: 61%
“…Two thirds of the population were younger than 50 years. The procedure is described in detail in previous publications [22]. The ten year follow-up is now ongoing and full data for the Skövde cohort has been collected.…”
Section: Study Populationsmentioning
confidence: 99%